Apatisme Politik Generazi Z di Indonesia: Sebuah Systematic Literature Review tentang Ancaman terhadap Demokrasi - Anisa Nur Rohmah; Efri Susana; Medhina Alsyira Masloman; Reno Indra Adi Putra; Khoiriya Ulfa (CV. ITTC INDONESIA, 2026)
Political apathy among Generation Z has become a critical phenomenon threatening the quality of democracy in Indonesia. This Systematic Literature Review (SLR) examines 20 peerreviewed Indonesian academic journals published between 20202025, organized into five thematic clusters: (1) political apathy and participation of Generation Z, (2) social media and digital politics, (3) political trust and democratic threats, (4) political education and democratic literacy, and (5) young voter behavior and electoral dynamics. The results reveal that although Generation Z constitutes 22.85%–27.95% of Indonesia's total registered voters, levels of political apathy remain high due to distrust of political institutions, the influence of disinformation, digital polarization, and inadequate civic education. However, the Indonesia Gelap 2025 protest movement and increased digital activism signal a potential transition from passivity to active participation. Social media platforms particularly TikTok, Instagram, and X function as primary political information channels, yet also amplify echo chambers and fragmented political identities. This study concludes that political apathy poses a structural threat to Indonesian democracy and recommends strengthening digital literacy, inclusive civic education, and participatory governance reforms as key interventions.